2007
DOI: 10.1007/s12098-007-0113-z
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung disease in infancy

Abstract: CMV Infection was the commonest cause of ILD in infancy in our study. However, the consequences on long term follow up in these infants need to be ascertained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…These findings indicated a high percentage of HCMV infection in patients with unresolved pneumonia. For anatomical classification of pneumonia with acute HCMV infection, the percentage of interstitial pneumonia and bronchiolitis cases with acute HCMV infection was high, similar to a previous report (Table 2) [23]. …”
Section: Resultssupporting
confidence: 88%
“…These findings indicated a high percentage of HCMV infection in patients with unresolved pneumonia. For anatomical classification of pneumonia with acute HCMV infection, the percentage of interstitial pneumonia and bronchiolitis cases with acute HCMV infection was high, similar to a previous report (Table 2) [23]. …”
Section: Resultssupporting
confidence: 88%
“…Thirty three studies reported morbidity, treatment and/or outcomes associated with chILD (Supplementary material, S2). Thirteen studies described chILD disorders as a group and 20 studies described specific chILD disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies from developed countries that reported mortality included patient groups with variable periods of follow‐up, extending to 17 or 18 years of age. Two studies from India (excluded from Table ), with patients aged less than two years, reported mortality rates of 33% and 75% . For studies conducted in developed countries with cohorts spanning childhood and adolescence, mortality ranged from 6% to 19% (median, 13%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations